2018
DOI: 10.1155/2018/5926906
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Pigment Dispersion Syndrome and Pigmentary Glaucoma: New Insights into Mechanisms

Abstract: We explore the ideas and advances surrounding the genetic basis of pigment dispersion syndrome (PDS) and pigmentary glaucoma (PG). As PG is the leading cause of nontraumatic blindness in young adults and current tailored interventions have proven ineffective, a better understanding of the underlying causes of PDS, PG, and their relationship is essential. Despite PDS being a subclinical disease, a large proportion of patients progress to PG with associated vision loss. Decades of research have supported a genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 120 publications
0
10
0
3
Order By: Relevance
“…In glaucoma, the role of complement in RGC synapse remodeling and monocyte infiltration has largely been investigated in the DBA/2J model 25,27,28 , which is a wellcharacterized model of disease that exhibits many similarities to human disease, including age-dependent progression and sectorial loss 93 . However, it is possible that such immune and/or inflammatory responses are influenced by the loss of function mutation in Gpnmb, which is expressed in myeloid cell lineages, as recently reviewed 94 .…”
Section: Complement Inhibition Restricts Onset and Progression Of Axomentioning
confidence: 99%
“…In glaucoma, the role of complement in RGC synapse remodeling and monocyte infiltration has largely been investigated in the DBA/2J model 25,27,28 , which is a wellcharacterized model of disease that exhibits many similarities to human disease, including age-dependent progression and sectorial loss 93 . However, it is possible that such immune and/or inflammatory responses are influenced by the loss of function mutation in Gpnmb, which is expressed in myeloid cell lineages, as recently reviewed 94 .…”
Section: Complement Inhibition Restricts Onset and Progression Of Axomentioning
confidence: 99%
“…It is reported that it affects Caucasians more often than other races [1,9,11]. Many cases are sporadic; however, there are families with apparent autosomal dominant inheritance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Pigmentary glaucoma is an important type of secondary open‐angle glaucoma (OAG) found in patients with the predisposing disease pigment dispersion syndrome (PDS). The development of pigmentary glaucoma from PDS is primarily attributed to sloughed pigment granules that deposit and accumulate in the trabecular meshwork, obstructing outflow . Traditionally, early treatment options have been similar to POAG with ocular hypotensive agents, although laser peripheral iridotomy has been suggested as an alternate first‐line treatment for pigmentary glaucoma intraocular pressure (PG IOP) elevation.…”
Section: Introductionmentioning
confidence: 99%